1996
DOI: 10.1103/physrevb.54.r2323
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field domain formation in type-II superlattices

Abstract: Static electric-field domains as well as current self-oscillations due to domain-wall oscillations have been observed in undoped, type-II GaAs-AlAs superlattices under photoexcitation. Photoluminescence measurements clearly demonstrate the coexistence of low-and high-field domains in the static and oscillating domain voltage regime. A comparison with the calculated energy level distribution indicates that the static domains are connected with negative differential velocity ͑NDV͒ due to resonant transfer betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Under the right conditions, such structures have current-voltage characteristics with regions of negative differential resistance ͑NDR͒, leading to a range of important possible applications. Many interesting phenomena related to the NDR have been found in superlattices ͑SLs͒, ranging from a sawtoothlike branch of the current-voltage characteristic on the sequential resonance tunneling plateau, [5][6][7][8][9][10] current self-oscillations, [11][12][13] and chaos.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under the right conditions, such structures have current-voltage characteristics with regions of negative differential resistance ͑NDR͒, leading to a range of important possible applications. Many interesting phenomena related to the NDR have been found in superlattices ͑SLs͒, ranging from a sawtoothlike branch of the current-voltage characteristic on the sequential resonance tunneling plateau, [5][6][7][8][9][10] current self-oscillations, [11][12][13] and chaos.…”
mentioning
confidence: 99%
“…[10][11][12] The oscillation can be induced by continuous illumination of a laser light 13 or by a change of doping. 11 Recently, it has been shown that this selfoscillation can also be induced by applying an external magnetic field parallel to the SL layers or by varying temperature.…”
mentioning
confidence: 99%
“…14 Self-oscillation has been observed in both doped and undoped SL systems. [10][11][12] The oscillation can be induced by continuous illumination of a laser light 13 or by change of doping. 11 Recently, it has been shown that this self-oscillation can also be induced by applying an external magnetic field parallel to the SL layers.…”
mentioning
confidence: 99%
“…Under the right conditions, such structures have current-voltage characteristics with regions of negative differential resistance ͑NDR͒, leading to a range of important possible applications. Many interesting phenomena related to the NDR have been found in superlattices ͑SL͒, ranging from current-voltage oscillations on the sequential resonance tunneling plateau, [5][6][7][8][9][10] current self-oscillations, [11][12][13] and chaos. 14 Self-oscillation has been observed in both doped and undoped SL systems.…”
mentioning
confidence: 99%
“…[6][7][8] In these studies the X states of the AlAs barriers were important in engineering long recombination times. Previous observations of photocurrent selfoscillations have been restricted to the GaAs-AlAs material system.…”
mentioning
confidence: 99%